A “Black Box” of Stakeholder Thinking - Pajunen, Kalle (Journal of business ethics, 2010)
The existence of a firm can be seen as a necessary condition for the existence of stakeholders. However, in the stakeholder literature, the firm has remained a relatively underdeveloped and fuzzy construct. In this essay, we examine how the firm has been conceptualized (explicitly or implicitly) in earlier research and suggest that, at least in stakeholder thinking, the firm can be considered as having an emergent nature. We elaborate this idea by building on the resent philosophical discussions of emergence and, as a result, propose the emergentist stakeholder model of the firm.